Calibration of engine parameters and fuel blend for vibration and noise characteristics in CRDI engine fuelled with low viscous biofuel. (15th March 2021) - Ashok, B.; Jeevanantham, A.K.; Vignesh, R.; Bhat Hire, Kartik R.; Prabhu, K.; Raaj Kumar, R.A.; Shivshankar, N.; Edwin Sudhagar, P.
Graphical abstract: Highlights: OPO blends is analyzed for vibro-acoustic and combustion characteristics for engine during idling. Advanced calibration approach of Central Composite Design & Response Surface Methodology used for optimizing the output. Vibration and Noise characteristics for the oxygenated Orange Peel Oil fuel. Abstract: An increasing number of on-road vehicles have increased the average duration of the engine's low-load and speed operation. This prolonged status of engine running is called idling and is the source of higher fuel consumption, increased engine wear, and spiked emissions. Also, to address the twin crisis of fossil fuel scarcity and higher engine-out emissions the present-day vehicles need suitable alternate fuels. Blending of Orange Peel Oil (OPO) with diesel is a promising solution to contain the reparations caused by idling emissions and fuel consumption. However, to ensure complete functionality of the OPO-diesel blend during idling, the combustion, vibrations, and sound characteristics need to be analysed. Hence, the present work calibrates the engine operating parameters for vibro-acoustic and combustion characteristics of a commercial vehicle diesel operating under idling conditions for pure diesel and OPO blends (10% and 20%). Vibrations, sound levels, and combustion characteristics were measured for diesel, OPO 10, and OPO 20 fuel blends. Experiments were conducted as per the Design of Experiments determined by Central Composite Design and the engine parameters were calibrated based on the optimised results using Response Surface Methodology. The results revealed that OPO20 performs better than OPO10 compared to pure diesel, as it displayed similar vibration characteristics and improved heat release rate by 8% while maintaining the same noise levels. The only deviation in vibration behaviour is at the engine mount which reported of 77% average increase along all three axes, while vibration in all other test points varied within a range of 5%.